Effect of solution treatment on high temperature oxidation of Fe-33Ni-19Cr and Fe-40Ni-24Cr alloys - Parimin, Noraziana (2015)
Nickel-based superalloys have the ability to form protective surface oxide scales at high temperature that provides them with resistance against further high temperature oxidation. In this research two types of nickel-based alloys namely, Fe-33Ni-19Cr and Fe-40Ni-24Cr were solution treated to vary the austenite grain size in order to observe its effect on the oxidation properties. The alloys were heat treated at temperatures of 950ºC, 1000ºC, 1050ºC, 1100ºC, 1150ºC and 1200ºC for 3 hours followed by water quench. The untreated and heat treated alloys were then subjected to high temperature oxidation under isothermal and cyclic condition for 500 hours and 150 cycles respectively in a specially designed oxidation rig. Thermogravimetric analysis in high purity oxygen was also performed on the alloys. The alloys were then analysed using optical microscope, scanning electron microscope, energy dispersive spectrometer and X-ray diffractometer. The results show that the oxide scales formed consist of various metal-based oxides with thickness of 1 μm to 10 μm. Both alloys show parabolic growth indicating the oxide was formed based on diffusion-controlled mechanism. It was found that the heat treatment processes at 950ºC, 1000ºC and 1050ºC produced fine austenite grains of 55 – 61 μm for Fe-33Ni-19Cr and 27 – 33 μm for Fe-40Ni-24Cr alloys. Alloys treated at 1100ºC, 1150ºC and 1200ºC produced coarse austenite grains of 65 – 100 μm for Fe-33Ni-19Cr and 36 – 41 μm for Fe-40Ni-24Cr alloys. Both alloys with fine austenite grains exhibited lower oxidation rate in isothermal and cyclic oxidation tests. This is due to the availability of ion diffusion path within the grain boundaries of fine grain alloys and hence allows the rapid formation of the protective oxide layer. Therefore, these alloys can be used for high temperature applications.